Answer:
x = -3
General Formulas and Concepts:
Pre-Algebra
- Order of Operations: BPEMDAS
- Equality Properties
Explanation:
Step 1: Define equation
12x + 20 = 5x - 10 - 3x
Step 2: Solve for x
- Combine like terms: 12x + 20 = 2x - 10
- Subtract 2x on both sides: 10x + 20 = -10
- Subtract 20 on both sides: 10x = -30
- Divide 10 on both sides: x = -3
Step 3: Check
Plug in x into the original equation to verify it is a solution.
- Substitute in x: 12(-3) + 20 = 5(-3) - 10 - 3(-3)
- Multiply: -36 + 20 = -15 - 10 + 9
- Add: -16 = -15 - 1
- Subtract: -16 = -16
Here we see that -16 does indeed equal -16.
∴ x = -3 is a solution of the equation.